Secondary battery and electric device
Patent Information
- Application Number
- CN202411215915.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-08-30
AI Technical Summary
While improving energy density and kinetic performance, existing secondary batteries are difficult to take into account high cycling performance and excellent kinetic performance.
The structure of the negative electrode film layer is optimized by using the first artificial graphite and the second artificial graphite having a specific crystallite size and graphitization degree in the negative electrode sheet, respectively, as the negative electrode active materials in the first and second regions, and by adjusting the powder OI value, particle size distribution and compaction density.
The high energy density, excellent dynamic performance and good cycle performance of the secondary battery are achieved, and the overall performance of the battery is improved.
Smart Images

Figure CN119852320A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Art
[0002] In recent years, as the application scope of secondary batteries has become more and more extensive, secondary batteries are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, aerospace and other fields. With the rapid development of secondary batteries, people have also put forward higher requirements for their energy density, dynamic performance, etc. Summary of the invention
[0003] The present application is made in view of the above problems, and its purpose is to provide a secondary battery and an electric device. The secondary battery of the present application has high energy density, excellent dynamic performance and good cycle performance.
[0004] In order to achieve the above object, the present application provides a secondary battery, comprising a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer comprising a first region and a second region, the first region being located between the second region and the negative electrode current collector, the first region comprising a first negative electrode active material, the second region comprising a second negative electrode active material, the powder OI value of the second negative electrode active material being less than the powder OI value of the first negative electrode active material, the first negative electrode active material comprising a first artificial graphite, the La(110) of the first artificial graphite being 130nm-175nm, and the Lc(002) being 30nm-42nm, La(110) representing the crystallite size along the a-axis in the (110) crystal plane of the first artificial graphite, and Lc(002) representing the crystallite size along the c-axis in the (002) crystal plane of the first artificial graphite. Thus, the secondary battery can have both high energy density and excellent kinetic performance.
[0005] In some embodiments, the La(110) of the first artificial graphite is 132nm-172nm, and / or the Lc(002) is 30nm-36nm, which is beneficial for the secondary battery to have a high energy density.
[0006] In some embodiments, La(110) / Lc(002) is 3.5-5.5, which is beneficial to improve the energy density of the secondary battery.
[0007] In some embodiments, La(110) / Lc(002) is 4.5-5.5. This is beneficial to increase the gram capacity of the first negative electrode active material and to increase the energy density of the secondary battery.
[0008] In some embodiments, a charge and discharge test is performed on a button cell prepared from the first artificial graphite at a lithium removal rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V, and in the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for more than 43% of the total discharge capacity of the button cell. Thus, the first artificial graphite has a high gram capacity, which is conducive to improving the energy density of the secondary battery.
[0009] In some embodiments, the discharge capacity corresponding to the lithium embedded platform accounts for 43%-47% of the total discharge capacity of the button cell. Thus, the first artificial graphite has a high gram capacity, which is beneficial to improving the energy density of the secondary battery.
[0010] In some embodiments, the gram capacity of the first negative electrode active material is greater than or equal to the gram capacity of the second negative electrode active material. In some embodiments, the gram capacity of the first negative electrode active material is ≥359mAh / g; and / or, the gram capacity of the second negative electrode active material is 353mAh / g-359mAh / g. As a result, it is beneficial to improve the kinetic performance of the secondary battery while taking into account the improvement of the energy density of the secondary battery. In some embodiments, the gram capacity of the first negative electrode active material is 359mAh / g-366mAh / g; and / or, the gram capacity of the second negative electrode active material is 354.6mAh / g-356.8mAh / g.
[0011] In some embodiments, the graphitization degree of the first negative electrode active material is greater than the graphitization degree of the second negative electrode active material. In some embodiments, the graphitization degree of the first negative electrode active material is 94.0%-96.0%; and / or, the graphitization degree of the second negative electrode active material is 93.5%-95.5%. It is beneficial for the first negative electrode active material to have a high compaction density and gram capacity, improve the transmission efficiency of active ions in the second negative electrode active material, and thus improve the energy density and kinetic performance of the secondary battery.
[0012] In some embodiments, the degree of graphitization of the first negative electrode active material is 94.2%-95.8%; and / or the degree of graphitization of the second negative electrode active material is 93.7%-95.3%.
[0013] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000 N is greater than the powder compaction density of the second negative electrode active material under a pressure of 50000 N. This is beneficial to improve the energy density of the secondary battery and enhance the kinetic performance of the secondary battery.
[0014] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50,000 N is 1.95 g / cc-2.04 g / cc; and / or the powder compaction density of the second negative electrode active material under a pressure of 50,000 N is 1.75 g / cc-1.94 g / cc.
[0015] In some embodiments, the first artificial graphite includes secondary particles, which is beneficial to improving the isotropy of the first negative electrode active material, reducing reversible expansion, and improving cycle performance.
[0016] In some embodiments, the powder OI value of the first negative electrode active material is 5.0-20.5; and / or the powder OI value of the second negative electrode active material is 2.5-6.5. This is conducive to dispersing the expansion of lithium insertion, thereby improving the cycle performance of the secondary battery. In addition, it is conducive to improving the isotropy of the second negative electrode active material and improving the dynamic performance of the secondary battery.
[0017] In some embodiments, the powder OI value of the first negative electrode active material is 5.5-19.5; and / or the powder OI value of the second negative electrode active material is 2.8-6.3.
[0018] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 10.0 μm-15.5 μm; and / or the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.95-1.3. This is beneficial to improving the kinetic performance of the secondary battery.
[0019] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 11.0 μm-14.5 μm; and / or the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.95-1.25.
[0020] In some embodiments, in the second negative electrode active material, the volume distribution of particles with a particle size greater than 6.5 μm and less than 22.5 μm accounts for ≥ 75%, thereby improving the compaction density of the negative electrode film layer and thus improving the energy density of the secondary battery.
[0021] In some embodiments, in the second negative electrode active material, the volume distribution of particles having a particle size greater than 6.5 μm and less than 22.5 μm accounts for 75%-90%.
[0022] In some embodiments, the second negative electrode active material includes a second artificial graphite and a third artificial graphite, wherein the second artificial graphite includes primary particles and the third artificial graphite includes secondary particles, thereby facilitating the second negative electrode active material to have both excellent kinetic performance and high energy density.
[0023] In some embodiments, in the second negative electrode active material, the mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 3:7. This is beneficial for the second negative electrode active material to have good kinetic performance, high energy density and good cycle performance.
[0024] In some embodiments, in the second negative electrode active material, a mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 1:3.
[0025] In some embodiments, the La(110) of the first artificial graphite is greater than the La(110) of the second artificial graphite, and the La(110) of the first artificial graphite is greater than the La(110) of the third artificial graphite. In some embodiments, the La(110) of the second artificial graphite is 100-140nm, and the Lc(002) is 25-32nm. In some embodiments, the La(110) of the third artificial graphite is 90-130nm, and the Lc(002) is 26-34nm. As a result, it is beneficial to maintain a better pore distribution of the negative electrode plate and improve the dynamic performance of the battery cell.
[0026] In some embodiments, the volume distribution particle size Dv50 of the second artificial graphite is 7 μm-9 μm, and Dv1 is 3 μm-5.5 μm; and / or the volume distribution particle size Dv50 of the third artificial graphite is 13 μm-18 μm. This is beneficial to improve the kinetic performance of the secondary battery and increase the energy density of the secondary battery.
[0027] In some embodiments, the powder OI value of the second artificial graphite is 7-10; and / or the powder OI value of the third artificial graphite is 2-5. This is beneficial to improving the kinetic performance and cycle performance of the secondary battery.
[0028] In some embodiments, the gram capacity of the second artificial graphite is 354.1 mAh / g to 359.6 mAh / g; and / or the gram capacity of the third artificial graphite is 353.0 mAh / g to 358.2 mAh / g. This is beneficial to improving the energy density of the secondary battery.
[0029] In some embodiments, the second artificial graphite has a powder compaction density of 1.72 g / cc to 1.92 g / cc at a pressure of 50,000 N; and / or the third artificial graphite has a powder compaction density of 1.75 g / cc to 1.95 g / cc at a pressure of 50,000 N. This is beneficial to improving the compaction density of the negative electrode film layer, thereby improving the energy density of the secondary battery.
[0030] In some embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 14.5 μm-18.0 μm. This is beneficial to improve the energy density of the secondary battery. In some embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 15.0 μm-17.5 μm.
[0031] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first artificial graphite is 0.90-1.25. Thus, it is beneficial to improve the dynamics of the first artificial graphite. In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first artificial graphite is 0.90-1.20.
[0032] In some embodiments, the specific surface area of the first artificial graphite is 0.8 m 2 / g-2.1m 2 / g. This is beneficial to improving the initial coulombic efficiency and kinetic performance of the secondary battery. In some embodiments, the specific surface area of the first artificial graphite is 1.0 m 2 / g-1.9m 2 / g.
[0033] In some embodiments, the first negative electrode material and / or the second negative electrode active material further comprises silicon, thereby facilitating further improving the energy density of the secondary battery.
[0034] The second aspect of the present application provides an electric device, comprising the secondary battery of the first aspect of the present application. Since the electric device of the present application comprises the secondary battery provided by the present application, it has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a schematic diagram of an embodiment of the negative electrode plate of the present application.
[0036] Figure 2 It is a schematic diagram of a battery cell according to an embodiment of the present application.
[0037] Figure 3 yes Figure 2 An exploded view of a battery cell according to an embodiment of the present application is shown.
[0038] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.
[0039] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0040] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0041] Figure 7 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0042] Description of reference numerals:
[0043] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 battery cell; 51 shell; 52 electrode assembly; 53 top cover assembly; 10 negative electrode plate; 101 negative electrode current collector; 102 negative electrode film layer; 102a first surface; 102b second surface; 1021 first area; 1022 second area; 1023 middle area. DETAILED DESCRIPTION
[0044] Below, the embodiments of the secondary battery and the electrical device of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0045] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0046] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0047] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0048] If not specifically stated, the terms used in this application have the commonly known meanings generally understood by those skilled in the art.
[0049] If not otherwise specified, the values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in this application.
[0050] If not otherwise specified, in the present application, the term "active ions" refers to ions that can be intercalated and extracted back and forth between the positive electrode and the negative electrode of a secondary battery, including but not limited to lithium ions.
[0051] At present, in order to obtain secondary batteries with high kinetics, there are reports proposing surface coating and other treatments on graphite materials. However, the use of surface coating methods leads to a decrease in the material's gram capacity and the compaction density of the electrode, affecting the energy density of the secondary battery.
[0052] Based on this, the present application proposes a secondary battery and an electrical device, thereby enabling the secondary battery to have both high energy density and excellent dynamic performance.
[0053] The present application has no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium-ion battery.
[0054] Generally, a secondary battery cell includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the secondary battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0055] Negative electrode
[0056] In the secondary battery of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode film layer located on at least one surface of the negative electrode current collector, the negative electrode film layer includes a first region and a second region, the first region is located between the second region and the negative electrode current collector, the first region includes a first negative electrode active material, the second region includes a second negative electrode active material, the powder OI value of the second negative electrode active material is less than the powder OI value of the first negative electrode active material, the first negative electrode active material includes a first artificial graphite, the La(110) of the first artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the carbon material, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the carbon material.
[0057] In the present application, the negative electrode film layer includes a first region and a second region, the first region is located between the second region and the negative electrode current collector, that is, the first region is located on the side of the negative electrode film layer close to the negative electrode current collector, and the second region is located on the side of the negative electrode film layer away from the negative electrode current collector. Figure 1 A schematic diagram of an embodiment of the negative electrode sheet of the present application is shown. Figure 1As shown, the negative electrode sheet 10 includes a negative electrode current collector 101 and a negative electrode film layer 102 formed on at least one surface of the negative electrode current collector 101, the negative electrode film layer 102 has a first surface 102a away from the negative electrode current collector 101 and a second surface 102b arranged opposite to the first surface 102a, and the thickness of the negative electrode film layer 102 is recorded as H. The thickness H of the negative electrode film layer refers to the thickness of the negative electrode film layer located on one side of the negative electrode current collector. The area within the range of 0.3H thickness from the second surface 102b of the negative electrode film layer is recorded as the first area 1021 of the negative electrode film layer. The area within the range of 0.3H thickness from the first surface 102a of the negative electrode film layer is recorded as the second area 1022 of the negative electrode film layer. The first area 1021 includes a first negative electrode active material, and the second area 1022 includes a second negative electrode active material. The area between the first area 1021 and the second area 1022 is recorded as the middle area 1023. It is easy to understand that within the scope of the middle region 1023, there may be only the first negative electrode active material, only the second negative electrode active material, both the first negative electrode active material and the second negative electrode active material, or other negative electrode active materials known in the art in addition to the first negative electrode active material and the second negative electrode active material of the present application.
[0058] It should be understood that Figure 1 In the embodiment shown in FIG. 1 , the second surface 102 b contacts the upper surface of the negative electrode current collector 101 , but the structure of the negative electrode sheet of the present application is not limited thereto. For example, there may be an additional layer between the negative electrode film layer 102 and the negative electrode current collector 101 . In this case, the second surface 102 b does not directly contact the negative electrode current collector 101 .
[0059] It should also be understood that Figure 1 Although the graphic shows clear boundaries between areas, there may not be such clear interfaces in the product.
[0060] In the present application, by setting the negative electrode film layer as a double layer, the negative electrode plate can still maintain a good pore structure, low tortuosity, a short ion transmission path and a high ion conduction efficiency at a higher compaction density, which is conducive to the secondary battery being able to take into account both high energy density and excellent kinetic performance. In addition, by making the powder OI value of the second negative electrode active material located in the second region less than the powder OI value of the first negative electrode active material located in the first region, the negative electrode active material located in the second region preferentially embeds active ions, which is conducive to the negative electrode film layer maintaining excellent kinetic performance. As a result, it is conducive to the secondary battery taking into account both high energy density and excellent kinetic performance.
[0061] In the present application, the first negative electrode active material includes a first artificial graphite, the La(110) of the first artificial graphite is 130nm-175nm, and the Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the carbon material, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the carbon material.
[0062] In the present application, the increase in La of artificial graphite indicates that the size of artificial graphite crystallites increases, and the number of sites that can be embedded with lithium on the surface of artificial graphite increases, so that the gram capacity increases. In addition, the increase in crystallite size can also reduce the number of grain boundaries of artificial graphite crystallites, so that the number of sites that can be embedded with lithium increases, thereby reducing the adverse effects on gram capacity and powder compaction density, and thus improving the gram capacity and powder compaction density of artificial graphite. The Lc of artificial graphite is within the above range, which is conducive to reducing the stacking of graphite crystallites, thereby reducing the number of grain boundaries between crystallites, and is conducive to increasing the number of lithium embedded sites on the surface of artificial graphite, thereby improving the gram capacity of artificial graphite. By making the La (110) and Lc (002) of the first artificial graphite within the above specific range, the development of graphite grains in the material is better, which is conducive to the embedding of active ions, thereby being able to improve the gram capacity of the first negative electrode active material. The negative electrode active material located in the first region has a high gram capacity and a high compaction density, which is conducive to the secondary battery having a high energy density. Exemplarily, La(110) of the first artificial graphite may be 130nm, 135nm, 140nm, 145nm, 150nm, 155nm, 160nm, 165nm, 170nm, 175nm or a value between the ranges consisting of any two of them. In addition, Lc(002) of the first artificial graphite may be 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 42nm or a value between the ranges consisting of any two of them.
[0063] In some embodiments, the La(110) of the first artificial graphite is 132nm-172nm, and / or the Lc(002) is 30nm-36nm. By making the La(110) and Lc(002) of the first artificial graphite within the above range, it is beneficial to increase the gram capacity and compaction density of the first negative electrode active material, thereby facilitating the secondary battery to have a high energy density.
[0064] In some embodiments, the La(110) / Lc(002) of the first artificial graphite is 3.5-5.5. The larger the La(110) / Lc(002), the better the grain development in the graphite material, the fewer the number of crystallites, and therefore the fewer the grain boundaries between the grains, which is beneficial to increasing the number of lithium-insertable sites on the surface of the artificial graphite, thereby facilitating increasing the gram capacity of the negative electrode active material. The present application enables the La(110) / Lc(002) of the first artificial graphite to be within the above range, which is beneficial to increasing the gram capacity of the first negative electrode active material, thereby increasing the energy density of the secondary battery. Exemplarily, La(110) / Lc(002) can be 3.5, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.5 or a value between the ranges consisting of any two of them. In some optional embodiments, in the first artificial graphite, La(110) / Lc(002) is 4.5-5.5.
[0065] In some embodiments, charge and discharge tests are performed on a button cell prepared from the first artificial graphite at a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the discharge capacity corresponding to the lithium insertion platform accounts for a proportion X of more than 43% of the total discharge capacity of the button cell.
[0066] In the present application, the charge and discharge test is carried out by the following method: the sample powder is mixed with the conductive agent carbon black (SuperP), the binder polyvinylidene fluoride (PVDF) and the solvent N-methylpyrrolidone (NMP) in a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, and dried in an oven for use; ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare a concentration of 1 mol l / L electrolyte; then use metal lithium sheet as counter electrode, polyethylene (PE) film as isolation membrane, and assemble into CR2430 button cell with the above electrolyte in an argon protected glove box; after the obtained button cell is allowed to stand for 12 hours, it is discharged at a constant current of 0.05C at 25°C to 0.005V, allowed to stand for 5 minutes, and discharged again at a constant current of 50μA to 0.005V, allowed to stand for 5 minutes, and then discharged again at a constant current of 10μA to 0.005V; then it is charged at a constant current of 0.1C to 2.0V, and the relationship between the charge and discharge capacity and voltage of the carbon material, that is, the charge and discharge curve, is obtained.
[0067] In the present application, a button cell prepared from the first artificial graphite is subjected to the above-mentioned charge and discharge test to obtain a charge and discharge curve. In the discharge curve, the discharge capacity corresponding to the lithium insertion platform in the voltage range of 0.005V to 0.070V accounts for more than 43% of the total discharge capacity of the button cell. The first artificial graphite has a high gram capacity, which is beneficial to improving the energy density of the secondary battery. Although the mechanism is not yet clear, the inventors believe that during the lithium insertion process of the graphite material, as the amount of lithium ion insertion increases, graphite intercalation compounds of different orders, such as LiC24, LiC12, LiC6, etc., will gradually form. The formation of graphite intercalation compounds of different orders corresponds to lithium insertion platforms in different voltage ranges in the charge and discharge curve of the graphite material. Since the theoretical capacity of graphite intercalation compounds of different orders is different, for example, the theoretical capacity of LiC6 is 372mAh / g, while the theoretical specific capacity of LiC12 is 186mAh / g. Therefore, in the lithium insertion process, the more LiC6 (i.e., the lithium insertion platform corresponding to the voltage range of 0.005V-0.07V) is formed, the more the corresponding capacity contribution is, and the higher the gram capacity of the graphite material is. Exemplarily, the ratio X can be 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50% or a value between the ranges consisting of any two of them. In some embodiments, the ratio X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button battery is 43%-50%, optionally 43%-47%.
[0068] In some embodiments, the gram capacity of the first negative electrode active material located in the first region is greater than or equal to the gram capacity of the second negative electrode active material located in the second region, thereby helping to improve the energy density of the secondary battery. The gram capacity of the first negative electrode active material is 359 mAh / g or more. By making the gram capacity of the first negative electrode active material within the above range, it is beneficial to increase the gram capacity of the negative electrode film layer, thereby improving the energy density of the secondary battery. Exemplarily, the gram capacity of the first negative electrode active material can be 359 mAh / g, 360 mAh / g, 361 mAh / g, 362 mAh / g, 363 mAh / g, 364 mAh / g, 365 mAh / g, 366 mAh / g, 367 mAh / g, 368 mAh / g, 369 mAh / g, 370 mAh / g or a value between the ranges consisting of any two of them. In some optional embodiments, the gram capacity of the first negative electrode active material is 359 mAh / g to 366 mAh / g.
[0069] In some embodiments, the gram capacity of the second negative electrode active material is 353mAh / g-359mAh / g. By making the gram capacity of the second negative electrode active material within the above range, it is beneficial to improve the kinetic performance of the secondary battery while taking into account the improvement of the energy density of the secondary battery. Exemplarily, the gram capacity of the second negative electrode active material can be 353mAh / g, 354mAh / g, 355mAh / g, 356mAh / g, 357mAh / g, 358mAh / g, 359mAh / g or a value between the ranges consisting of any two of them. In some optional embodiments, the gram capacity of the second negative electrode active material is 354.6mAh / g-356.8mAh / g.
[0070] In some embodiments, the degree of graphitization of the first negative electrode active material is greater than the degree of graphitization of the second negative electrode active material. The degree of graphitization of the first negative electrode active material is 94.0%-96.0%. By making the degree of graphitization of the first negative electrode active material in the above range, it is beneficial for the first negative electrode active material to have a high compaction density and gram capacity, thereby improving the energy density of the secondary battery. Exemplarily, the degree of graphitization of the first negative electrode active material can be 94.0%, 94.5%, 95.0%, 95.5%, 96.0% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the first negative electrode active material is 94.2%-95.8%.
[0071] In some embodiments, the degree of graphitization of the second negative electrode active material is 93.5%-95.5%. By making the second negative electrode active material in the above range, it is beneficial to improve the transmission efficiency of active ions in the second negative electrode active material, thereby improving the kinetic performance of the secondary battery. Exemplarily, the degree of graphitization of the second negative electrode active material can be 93.5%, 94.0%, 94.5%, 95.0%, 95.5% or a value between the ranges consisting of any two of them. In some optional embodiments, the degree of graphitization of the second negative electrode active material is 93.7%-95.3%.
[0072] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000 N is greater than the powder compaction density of the second negative electrode active material under a pressure of 50000 N. In the present application, the first negative electrode active material has a higher powder compaction density, which is beneficial to increase the gram capacity of the negative electrode film layer, thereby increasing the energy density of the secondary battery. The powder compaction density of the second negative electrode active material is lower than that of the first negative electrode active material, which is beneficial to improve the kinetic performance of the secondary battery.
[0073] In some embodiments, the powder compaction density of the first negative electrode active material under a pressure of 50000N is 1.95g / cc-2.04g / cc. By making the powder compaction density of the first negative electrode active material within the above range, it is beneficial to increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery. Exemplarily, the powder compaction density of the first negative electrode active material under a pressure of 50000N can be 1.95g / cc, 1.96g / cc, 1.97g / cc, 1.98g / cc, 1.99g / cc, 2.00g / cc, 2.01g / cc, 2.02g / cc, 2.03g / cc, 2.04g / cc or a value between any two of them.
[0074] In some embodiments, the powder compaction density of the second negative electrode active material under a pressure of 50000 N is 1.75 g / cc-1.94 g / cc. Exemplarily, the powder compaction density of the second negative electrode active material under a pressure of 50000 N may be 1.75 g / cc, 1.76 g / cc, 1.78 g / cc, 1.80 g / cc, 1.82 g / cc, 1.84 g / cc, 1.86 g / cc, 1.88 g / cc, 1.90 g / cc, 1.92 g / cc, 1.94 g / cc or a value between any two of them.
[0075] In some embodiments, the first artificial graphite includes secondary particles. The first artificial graphite is mainly composed of secondary particles, for example, more than 80% of the first artificial graphite particles are secondary particles, and illustratively, 80%, 85% or 90% of the first artificial graphite particles are secondary particles. This is conducive to improving the isotropy of the first negative electrode active material, reducing reversible expansion, and improving cycle performance.
[0076] In some embodiments, the powder OI value of the first negative electrode active material is 5.0-20.5. By making the powder OI value of the first negative electrode active material within the above range, it is beneficial to disperse the expansion of lithium insertion, thereby improving the cycle performance of the secondary battery. Exemplarily, the powder OI value of the first negative electrode active material can be 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10, 10.5, 11.0, 12.0, 13.0, 14.0, 15.0, 16.0, 17.0, 18.0, 19.0, 19.5, 20.0, 20.5 or a value between the ranges consisting of any two of them. In some optional embodiments, the powder OI value of the first negative electrode active material is 5.5-19.5.
[0077] In some embodiments, the powder OI value of the second negative electrode active material is 2.5-6.5, and the powder OI value is appropriate, which is conducive to improving the isotropy of the second negative electrode active material, and the active ions can be deintercalated from all directions, thereby increasing the number of deintercalation channels of the active ions in the second negative electrode active material particles, which is conducive to improving the kinetic performance of the secondary battery. Exemplarily, the powder OI value of the second negative electrode active material can be 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5 or a value between the ranges consisting of any two of them. In some embodiments, the powder OI value of the second negative electrode active material is 2.8-6.3.
[0078] In some embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 10.0μm-15.5μm. By making the volume distribution particle size Dv50 of the second negative electrode active material within the above range, it is beneficial to improve the transport performance of active ions and electrons of the second negative electrode active material in the negative electrode film layer, thereby further improving the kinetic performance of the secondary battery. Exemplarily, the distribution particle size Dv50 of the second negative electrode active material can be 10.0μm, 10.5μm, 11.0μm, 11.5μm, 12.0μm, 12.5μm, 13.0μm, 13.5μm, 14.0μm, 14.5μm, 15.0μm, 15.5μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the second negative electrode active material is 11.0μm-14.5μm.
[0079] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.95-1.3. As a result, it is beneficial to improve the compaction density of the negative electrode film layer and the energy density of the secondary battery; in addition, it is also beneficial to form a reasonable pore structure between the particles of the negative electrode film layer, improve the active ion and electron transport performance in the negative electrode film layer, and thus improve the kinetic performance of the secondary battery. Exemplarily, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25, 1.30 or a value between the ranges consisting of any two of them. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the second negative electrode active material is 0.95-1.25.
[0080] In some embodiments, in the second negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5μm and less than 22.5μm is greater than or equal to 75%. By making the volume distribution proportion of the second negative electrode active material within the above range, it is beneficial to improve the compaction density of the negative electrode film layer, thereby improving the energy density of the secondary battery. Exemplarily, in the second negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5μm and less than 22.5μm can be 75%, 80%, 85%, 90%, 95% or a value between the ranges consisting of any two of them. In some optional embodiments, in the second negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5μm and less than 22.5μm is 75%-90%.
[0081] In some embodiments, the second negative electrode active material includes a second artificial graphite and a third artificial graphite, the second artificial graphite includes primary particles, and the third artificial graphite includes secondary particles. By making the second negative electrode active material include primary particles of the second artificial graphite and secondary particles of the third artificial graphite, it is beneficial to make the second negative electrode active material have both excellent kinetic performance and high energy density. During the charging process of the secondary battery, the side away from the current collector preferentially embeds active ions. Therefore, by locating the second negative electrode active material in the second region, the kinetics of the secondary battery can be further improved.
[0082] In some embodiments, the second artificial graphite is mainly composed of primary particles, for example, more than 80% of the second artificial graphite particles are primary particles, and illustratively, 80%, 85% or 90% of the second artificial graphite particles are primary particles. The third artificial graphite is mainly composed of secondary particles, for example, more than 80% of the third artificial graphite particles are secondary particles, and illustratively, 80%, 85% or 90% of the third artificial graphite particles are secondary particles.
[0083] In some embodiments, in the second negative electrode active material, the mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 3:7. By making the mass ratio of the second artificial graphite to the third artificial graphite within the above range, it is beneficial to adjust the powder OI value and the powder compaction density of the second negative electrode active material, so that the second negative electrode active material can take into account good kinetic performance and high energy density as well as good cycle performance. Exemplarily, the mass ratio of the second artificial graphite to the third artificial graphite can be 3:7, 1:3, 1:4, 5:17, 1:9 or a value between the ranges consisting of any two ratios thereof. In some optional embodiments, the mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 1:3.
[0084] In some embodiments, the La(110) of the first artificial graphite is greater than the La(110) of the second artificial graphite, and the La(110) of the first artificial graphite is greater than the La(110) of the third artificial graphite. The La(110) of the second artificial graphite is 100-140nm, and the Lc(002) is 25-32nm. The La(110) of the third artificial graphite is 90-130nm, and the Lc(002) is 26-34nm. Thus, it is beneficial to take into account both higher gram capacity and kinetic performance.
[0085] In some embodiments, the volume distribution particle size Dv50 of the second artificial graphite is 7μm-9μm, and Dv1 is 3μm-5.5μm; illustratively, the volume distribution particle size Dv50 of the second artificial graphite is 7μm, 7.5μm, 8μm, 8.5μm, 9.0μm, Dv1 is 3.5μm, 4.0μm, 4.5μm, 5.0μm, 6.0μm, and optionally, Dv1 is 3.0μm-5.5μm. By making the particle size of the second artificial graphite within the above range, it is beneficial to reduce the distance of the solid phase diffusion path of the active ions in the primary particles, increase the deintercalation rate of the active ions, and thus improve the kinetic performance of the secondary battery; in addition, it is beneficial to increase the number of active ions embedded in the primary particles, thereby increasing the gram capacity of the negative electrode active material, and is beneficial to improve the energy density of the secondary battery. In some embodiments, the volume distribution particle size Dv50 of the third artificial graphite is 13μm-18μm. For example, it is 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, and 18 μm. By making the volume distribution particle size of the third artificial graphite within the above range, it is beneficial to improve the isotropy of the negative electrode active material, increase the number of deintercalation channels of active ions in the negative electrode active material, and improve the transmission efficiency of active ions and electrons, thereby improving the kinetic performance of the secondary battery.
[0086] In some embodiments, the powder OI value of the second artificial graphite is 7-10, exemplarily, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10 or a value between the ranges consisting of any two of them. By making the powder OI of the second artificial graphite within the above range, it is beneficial to improve the conductivity efficiency of the second negative electrode active material, thereby improving the kinetic performance and cycle performance of the secondary battery. In some embodiments, the powder OI value of the third artificial graphite is 2-5, exemplarily, 2, 3, 4, 5 or a value between the ranges consisting of any two of them. By making the powder OI value of the third artificial graphite within the above range, it is beneficial to improve the isotropy of the second negative electrode active material, increase the number of active ion deintercalation channels, and increase the number of active sites in the negative electrode film layer, thereby improving the kinetic performance of the secondary battery.
[0087] In some embodiments, the gram capacity of the second artificial graphite is 354.1mAh / g-359.6mAh / g; and / or, the gram capacity of the third artificial graphite is 353.0mAh / g-358.2mAh / g. By making the gram capacity of the second artificial graphite and / or the third artificial graphite within the above range, it is beneficial to increase the gram capacity of the negative electrode active material, thereby increasing the energy density of the secondary battery. Exemplarily, the gram capacity of the second artificial graphite is 354.1mAh / g, 355.2mAh / g, 356.3mAh / g, 357.4mAh / g, 358.5mAh / g, 359.6mAh / g or a value between the ranges consisting of any two of them. Exemplarily, the gram capacity of the third artificial graphite may be 353.0 mAh / g, 354.1 mAh / g, 355.2 mAh / g, 356.3 mAh / g, 357.4 mAh / g, 358.2 mAh / g or a value within a range consisting of any two of these values.
[0088] In some embodiments, the powder compaction density of the second artificial graphite under a pressure of 50,000 N is 1.72 g / cc-1.92 g / cc, and exemplary is 1.72 g / cc, 1.75 g / cc, 1.76 g / cc, 1.77 g / cc, 1.78 g / cc, 1.79 g / cc, 1.80 g / cc, 1.81 g / cc, 1.83 g / cc, 1.85 g / cc, 1.87 g / cc, 1.89 g / cc, 1.90 g / cc, 1.92 g / cc or a value within a range consisting of any two of them. In some embodiments, the powder compaction density of the third artificial graphite under a pressure of 50000N is 1.75 to 1.95 g / cc, illustratively, 1.75 g / cc, 1.76 g / cc, 1.77 g / cc, 1.78 g / cc, 1.79 g / cc, 1.80 g / cc, 1.81 g / cc, 1.83 g / cc, 1.85 g / cc, 1.87 g / cc, 1.89 g / cc, 1.90 g / cc, 1.92 g / cc, 1.95 g / cc or a value between the ranges consisting of any two of them. By making the powder compaction density of the second artificial graphite and / or the third artificial graphite within the above range, it is beneficial to increase the compaction density of the negative electrode film layer, thereby increasing the energy density of the secondary battery.
[0089] In some embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 14.5μm-18.0μm. Exemplarily, the volume distribution particle size Dv50 of the first artificial graphite can be 14.5μm, 15.0μm, 15.5μm, 16.0μm, 16.5μm, 17.0μm, 17.5μm, 18.0μm or a value between the ranges consisting of any two of them. In some optional embodiments, the volume distribution particle size Dv50 of the first artificial graphite is 15.0μm-17.5μm. Thus, it is beneficial to improve the powder compaction density of the first artificial graphite, thereby improving the energy density of the secondary battery.
[0090] In some embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first artificial graphite is 0.90-1.25. Exemplary, the particle size distribution (Dv90-Dv10) / Dv50 of the first artificial graphite is 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, 1.25 or the value between the ranges composed of any two of them. In some optional embodiments, the particle size distribution (Dv90-Dv10) / Dv50 of the first artificial graphite is 0.90-1.20. Thus, it is conducive to improving the dynamics of the first artificial graphite.
[0091] In some embodiments, the specific surface area of the first artificial graphite is 0.8 m 2 / g-2.1m 2 / g. By making the specific surface area of the first artificial graphite within the above range, on the one hand, the first artificial graphite can have a lower surface side reaction activity, thereby reducing the consumption of active ions in SEI film formation and improving the initial coulombic efficiency of the secondary battery; on the other hand, it can also have a higher active ion transport performance and improve the kinetic performance of the secondary battery. Exemplarily, the specific surface area of the first artificial graphite can be 0.8m 2 / g, 1.0m 2 / g, 1.2m 2 / g, 1.4m 2 / g, 1.6m 2 / g, 1.8m 2 / g, 2.0m 2 / g, 2.1m 2 / g or a value between any two of the values thereof. In some optional embodiments, the specific surface area of the first artificial graphite is 1.0 m 2 / g-1.9m 2 / g.
[0092] In some embodiments, the first negative electrode active material and / or the second negative electrode active material also include silicon. By adding silicon to the first negative electrode active material and / or the second negative electrode active material, it is beneficial to further improve the energy density of the secondary battery. Exemplarily, silicon can come from one or more of nano-silicon materials, silicon oxide materials, and silicon-carbon composite materials. In some embodiments, the content of silicon is less than or equal to 30wt% relative to the total mass of the negative electrode film layer. Exemplarily, the content of silicon can be 30wt%, 25wt%, 20wt%10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt%, 0.1wt% or a value between the ranges consisting of any two of them relative to the total mass of the negative electrode film layer. In some optional embodiments, the content of silicon is 3wt%-10wt% relative to the total mass of the negative electrode film layer.
[0093] In the present application, La (110) and Lc (002) of artificial graphite can be measured using instruments and methods known in the art. For example, the negative electrode plate removed from the secondary battery can be cleaned with an organic solvent such as DMC and then dried. The cleaned negative electrode plate is then immersed in NMP for ultrasonic treatment to separate the copper foil to obtain a negative electrode material. After the negative electrode material is dried, it is sintered at 350°C-500°C, then washed with water for multiple times, and dried at 80°C to obtain a negative electrode active material. The negative electrode active material is tested using an X-ray diffractometer (such as Bruker D8 Discover). The test can refer to JIS K 0131-1996 and JB / T4220-2011 to obtain the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (110) crystal plane of the carbon material, and the peak intensity and half-maximum full width (FWHM) of the diffraction peak corresponding to the (002) crystal plane, and then calculated according to the Scherrer formula.
[0094] In the present application, the OI value of the powder of the material (the first negative electrode active material, the second negative electrode active material, the first artificial graphite, the second artificial graphite, the third artificial graphite, etc.) refers to the graphite orientation of the material, which describes the orientation consistency of the crystals in the graphite material particles. The powder OI value of the material is the ratio of the peak area of the plane (004) to the peak area of the plane (110) obtained by testing the material by X-ray diffraction. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used for testing. The test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the X-ray diffraction spectrum of the powder sample. According to OI value = I 004 / I 110 The powder OI value of the sample is calculated. 004is the integrated area of the diffraction peak of the 004 crystal plane of crystalline carbon in the powder sample, I 110 is the integrated area of the diffraction peak of the crystalline carbon 110 crystal plane in the powder sample. In the X-ray diffraction analysis test of the present application, a copper target can be used as an anode target, and CuKα rays can be used as a radiation source with a wavelength of The scanning 2θ angle range was 20°-80°, and the scanning rate was 4° / min.
[0095] In the present application, the powder compaction density of the material (the first negative electrode active material, the second negative electrode active material, the first artificial graphite, the second artificial graphite, the third artificial graphite, etc.) is the mass per unit volume of the powder under specified conditions, which can be measured by instruments and methods known in the art. For example, it can be measured by an electronic pressure testing machine (for example, a UTM7305 electronic pressure testing machine) with reference to GB / T 24533-2009. The exemplary test method is as follows: weigh 1g of sample powder and add a bottom area of 1.327cm 2 In the mold, the pressure is increased to 50000N, the pressure is maintained for 30s, and then the pressure is released and maintained for 10s. Then the powder compaction density of the material under the pressure of 50000N is recorded and calculated.
[0096] In the present application, the volume distribution particle size Dv1, Dv10, Dv50, and Dv90 of the material (e.g., the first negative electrode active material, the second negative electrode active material, the first artificial graphite, the second artificial graphite, the third artificial graphite, etc.) respectively represent the particle size corresponding to the cumulative volume distribution percentage of the material reaching 1%, 10%, 50%, and 90%, which can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0097] In the present application, the volume distribution percentage of particles with a particle size greater than 6.5 μm and less than 22.5 μm can be determined by the following method: The particle size can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer with reference to GB / T 19077-2016. The volume distribution percentage X corresponding to a particle size less than or equal to 6.5 μm and the volume distribution percentage Y corresponding to a particle size less than 22.5 μm are tested. The volume distribution percentage of particles with a particle size greater than 6.5 μm and less than 22.5 μm is calculated using the formula (YX)*100%.
[0098] In the present application, the gram capacity of the material (first negative electrode active material, second negative electrode active material, first artificial graphite, second artificial graphite, third artificial graphite, etc.) is the ratio of the capacity that the active material can release to the mass of the active material, and can be tested by methods known in the art. An exemplary test method is as follows: the sample powder is mixed with a conductive agent, a binder and other optional additives in a certain mass ratio with a solvent to form a slurry; the prepared slurry is applied on the surface of the negative electrode current collector copper foil, and dried in an oven for use; the electrolytic salt is dissolved in an organic solvent to prepare an electrolyte of a certain concentration; then a metal lithium sheet is used as a counter electrode, a polyethylene (PE) film is used as a separator, and the electrolyte is assembled into a CR2430 button battery in an argon-protected glove box. After the button cell was left to stand for 12 hours, the button cell prepared above was first discharged to 0.005V at 0.15mA at 25°C, left to stand for 10 minutes, then discharged to 0.005V at 50μA, left to stand for 10 minutes, and then discharged to 0.005V at 10μA, and the first cycle discharge capacity of the button cell was recorded; then the button cell was charged to 2.0V at 0.3mA, and the first cycle charge capacity of the button cell was recorded. The ratio of the charge capacity to the sample mass is the gram capacity of the corresponding material (negative active material, first artificial graphite, second artificial graphite, third artificial graphite, etc.).
[0099] In the present application, the graphitization degree of the material (the first negative electrode active material, the second negative electrode active material, the first artificial graphite, the second artificial graphite, the third artificial graphite, etc.) is the proportion of carbon in the material in the form of a graphite structure, which can be tested using instruments and methods known in the art. For example, an X-ray diffractometer (such as Bruker D8Discover) can be used for testing, and the test can refer to JIS K 0131-1996 and JB / T 4220-2011 to obtain the average interlayer spacing d of the C(002) crystal plane in the material crystal structure. 002 Then according to the formula g = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree. In the above formula, d 002 It is the average interlayer spacing of the C(002) crystal plane in the material's crystal structure expressed in nanometers (nm).
[0100] In this application, the thickness of the negative electrode film layer has a well-known meaning in the art and can be tested by methods known in the art, such as using a micrometer (such as Mitutoyo 293-100, with an accuracy of 0.1 μm). The thickness range given in this application is the thickness range of the negative electrode film layer on one side of the negative electrode current collector.
[0101] In the present application, primary particles and secondary particles have the meanings known in the art. Primary particles refer to non-agglomerated particles. Secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be distinguished by using a scanning electron microscope (SEM) image.
[0102] Method for preparing negative electrode sheet
[0103] The negative electrode sheet in the present application can be prepared in the following manner: provide a first slurry containing a first negative electrode active material and a second slurry containing a second negative electrode active material; apply the first slurry on the negative electrode collector, apply the second slurry on the first slurry, and obtain the negative electrode sheet after drying and cold pressing.
[0104] The preparation method of the first negative electrode active material in the present application comprises the following steps:
[0105] The first step of preparing artificial graphite:
[0106] Pretreatment step: crushing and shaping the calcined needle coke to obtain a shaped material; the calcined needle coke has a carbon content of more than 97%, a volatile component content of less than 2%, and a sulfur content of less than 0.5%;
[0107] Granulation step: mixing the shaping material with a first adhesive to obtain a granulated material;
[0108] Graphitization step: subjecting the granulated material to a first graphitization treatment at 3000° C.-3200° C. to obtain a first artificial graphite with La(110) of 130nm-175nm and Lc(002) of 30nm-42nm as a first negative electrode active material.
[0109] In the present application, calcined needle coke is used as raw material. The needle structure of calcined needle coke is stronger and the mosaic structure is less. Using calcined needle coke as raw material is beneficial to reduce the content of impurities in artificial graphite, thereby improving the graphitization degree of artificial graphite.
[0110] In the present application, the carbon content of the calcined needle coke is more than 97%, the volatile component content is less than 2%, and the sulfur content is less than 0.5%. Here, the so-called volatile components refer to hydrocarbons with lower molecular weight, such as light alkanes. The sulfur content and volatile components of the calcined needle coke are within the above ranges, and the purity of the raw materials is good, which is conducive to the development of grains during graphitization, reduces the number of defects in the graphitization process, increases the graphitization degree of artificial graphite and the La (110) value of artificial graphite, thereby increasing the gram capacity and compaction density of the negative electrode film layer, and increasing the energy density of the secondary battery.
[0111] In the present application, the temperature of the graphitization treatment is 3000°C-3200°C. The graphitization temperature within the above range is conducive to the growth and development of graphite grains, thereby improving the La (110) value of the graphite material. In addition, it is also conducive to improving the graphitization degree of artificial graphite, thereby improving the gram capacity of the first artificial graphite and improving the energy density of the secondary battery. Exemplarily, the graphitization temperature can be 3000°C, 3050°C, 3100°C, 3150°C, 3200°C or a value between the ranges consisting of any two of them.
[0112] In the present application, high-purity raw materials are used and the graphitization temperature is controlled at 3000°C-3200°C, which is beneficial to the development of the 110 crystal planes of the graphite grains along the a-axis during the graphitization process, thereby increasing the La (110) value of the artificial graphite. In addition, it is also beneficial to reduce the number of defects in the graphitization process, thereby facilitating the improvement of the energy density of the secondary battery.
[0113] Those skilled in the art can adjust the graphitization time as needed. For example, an Acheson graphitization furnace can be used for graphitization treatment, and when the temperature is above 2800° C., the graphitization time can be 2-8 days.
[0114] In some embodiments, the volume distribution particle size Dv50 of the shaping material is 9 μm-13 μm. Controlling the volume distribution particle size Dv50 of the shaping material within the range of 9 μm-13 μm is conducive to reducing the number of grain boundaries between crystals in the formation of the grain boundary structure in the artificial graphite, thereby increasing the gram capacity and powder compaction density of the artificial graphite.
[0115] In some embodiments, the softening point of the first adhesive is 180°C-270°C. In the present application, the softening point can be tested using instruments and methods known in the art, for example, it can be measured with reference to GB / T4507-2014. When the softening point of the first adhesive is within the above range, the molecular weight of the condensed aromatic hydrocarbons in the first adhesive is large and the content is high, which is conducive to improving the adhesion of the first adhesive and reducing the amount of the first adhesive in the granulation step, thereby increasing the gram capacity and compacted density of the first artificial graphite. Exemplarily, the softening point of the first adhesive can be 180°C, 200°C, 220°C, 240°C, 260°C, 270°C or a value between the ranges consisting of any two of them.
[0116] In some embodiments, the coking value of the first adhesive is 50%-70%. In the present application, the coking value can be tested by a method known in the art. For example, it can be measured with reference to GB / T 8727-2008. The coking value of the first adhesive is within the above range, which is conducive to improving the gram capacity and compaction density of the first artificial graphite, thereby improving the energy density of the secondary battery.
[0117] In some embodiments, the mass ratio of the shaping material to the first adhesive is 100:(6-12). The ratio of the shaping material to the first adhesive within the above range is conducive to reducing the amount of residual carbon brought by the first adhesive, increasing the gram capacity and compaction density of the first artificial graphite, and thus improving the energy density of the secondary battery.
[0118] In some embodiments, before the graphitization step, the granulated material is pre-carbonized to obtain an intermediate. The pre-carbonization step is beneficial to reduce the volatile components in the first binder, thereby reducing the impurity content in the first artificial graphite, increasing the gram capacity and compaction density of the first artificial graphite, and improving the energy density of the secondary battery.
[0119] In some embodiments, the pre-carbonization temperature is 1000°C-1500°C. Exemplarily, the pre-carbonization temperature can be 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or a value between the ranges consisting of any two of them. By making the pre-carbonization temperature within the above range, the volatile components contained in the raw materials can be fully removed, which is beneficial to reduce the number of impurities and defects in the artificial graphite, thereby increasing the gram capacity of the artificial graphite. In addition, the pre-carbonization treatment can increase the density of the raw materials and increase the amount of raw materials loaded in the furnace during the graphitization process. In an optional embodiment, the pre-carbonization temperature is 1000°C-1100°C.
[0120] In some embodiments, the pre-carbonization time is 1-4 hours. Exemplary pre-carbonization time may be 1 hour, 2 hours, 3 hours, 4 hours, or a range consisting of any two of these values.
[0121] In some embodiments, the pre-carbonization is performed under a protective atmosphere, illustratively, the protective atmosphere may be nitrogen or argon. In an optional embodiment, the pre-carbonization is performed under a nitrogen atmosphere.
[0122] In some embodiments, the volume distribution particle size Dv50 of the intermediate is 15 μm-18 μm. The intermediate particle size within the above range is conducive to increasing the particle size of the first artificial graphite, thereby increasing the gram capacity of the first artificial graphite and improving the energy density of the secondary battery.
[0123] In some embodiments, the preparation method further comprises, after the graphitization step, subjecting the artificial graphite to surface micro-oxidation treatment. In the present application, the surface micro-oxidation treatment can be carried out by methods known in the art. Exemplarily, the surface micro-oxidation treatment can be carried out by subjecting the artificial graphite to an air atmosphere at 700°C for a treatment time of 1-4 hours. The surface micro-oxidation treatment of artificial graphite can increase oxidative functional groups on the surface of artificial graphite, enhance the bonding force between artificial graphite particles and between artificial graphite and a binder, and reduce the rebound effect, thereby facilitating the improvement of the powder compaction density of artificial graphite, and thereby improving the energy density of secondary batteries.
[0124] The preparation method of the second negative electrode active material in the present application comprises the following steps:
[0125] The second artificial graphite preparation step: crushing and shaping the second raw material with a sulfur content of less than or equal to 1.5% by mass, grading and screening, and then performing a second graphitization at 3000° C.-3200° C. to prepare primary particles as the second artificial graphite;
[0126] The third artificial graphite preparation step: crushing and shaping the third raw material with a sulfur content of less than or equal to 1.5% by mass to obtain primary particles, then adding a second adhesive to granulate, and performing a third graphitization at 3000° C.-3200° C. to obtain secondary particles as the third artificial graphite;
[0127] Mixing step: mixing the second artificial graphite and the third artificial graphite to obtain the second negative electrode active material; wherein the powder OI value of the second negative electrode active material is 2.5-6.5, and the powder compaction density of the negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
[0128] In the present application, in the above-mentioned second artificial graphite preparation step and / or the third artificial graphite preparation step, the second graphitization and / or the third graphitization is carried out at 3000° C.-3200° C. Exemplarily, the second graphitization and / or the third graphitization can be carried out at a temperature of 3000° C., 3050° C., 3100° C., 3150° C., 3200° C., or a value between the ranges consisting of any two of the values thereof.
[0129] Those skilled in the art can adjust the graphitization time as needed. In some embodiments, the treatment time of the second graphitization and / or the third graphitization can be 4-60 hours. For example, when the raw material is low-sulfur needle coke, the graphitization temperature is 3100°C, and the graphitization time can be 12 hours, 24 hours, or 36 hours.
[0130] By mixing the second artificial graphite and the third artificial graphite, the primary particle size of the second artificial graphite is small, the powder compaction density is high, and the secondary particle isotropy of the third artificial graphite is high, so that the powder OI value of the second negative electrode active material is 2.5-6.5, and the powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc, which is conducive to the high capacity, high compaction density and excellent dynamic performance of the second negative electrode active material, so that the secondary battery has high energy density and excellent dynamic performance. The second artificial graphite with a smaller particle size can be filled in the gap between the secondary particles of the third artificial graphite in the negative electrode active material, play a role in supporting and dispersing the secondary particles, improve the structural stability and processing performance of the second negative electrode active material, reduce the amount of dispersant and suspending agent in the negative electrode film layer, increase the active sites of the second negative electrode active material, thereby improving the dynamic performance of the secondary battery, and increase the proportion of negative electrode active materials in the second negative electrode film layer, thereby improving the energy density of the secondary battery.
[0131] In some embodiments, in the second artificial graphite preparation step, a second graphitization is performed to prepare primary particles with a volume distribution particle size Dv50 of 7μm-9μm and Dv1 of 3μm-5.5μm as the second artificial graphite. In the second artificial graphite preparation step, a classifier is used to classify and prepare primary particles with a volume distribution particle size Dv50 of 7μm-9μm and Dv1 of 3μm-5.5μm. The particle size of the primary particles is small, which is beneficial to reduce the distance of the solid phase diffusion path of the active ions in the primary particles, and improve the deintercalation rate of the active ions, thereby improving the kinetic performance of the secondary battery; and the volume distribution particle size Dv1 of the primary particles is 3μm-5.5μm, which is beneficial to increase the number of embedded active ions in the primary particles, thereby increasing the gram capacity of the second negative electrode active material, and is beneficial to improving the energy density of the secondary battery.
[0132] In some embodiments, in the preparation step of the third artificial graphite, the third raw material is crushed and shaped to obtain primary particles with a volume distribution particle size Dv50 of 7μm-9μm; then a binder is added for granulation, and a third graphitization is performed at 3000℃-3200℃ to obtain secondary particles with (Dv90-Dv10) / Dv50 of 1.0-1.25 and Dv50 of 13μm-18μm, thereby obtaining the third artificial graphite. In the preparation step of the third artificial graphite, preparing secondary particles with a Dv50 of 13μm-18μm is beneficial to improving the isotropy of the second negative electrode active material, increasing the number of active ion deintercalation channels in the second negative electrode active material, and improving the transmission efficiency of active ions and electrons, thereby improving the kinetic performance of the secondary battery.
[0133] In the present application, the second raw material and / or the third raw material can be raw materials known in the art that can be used to prepare artificial graphite, without special limitation. Exemplarily, the second raw material and / or the third raw material can include one or more of petroleum coke, calcined petroleum coke, needle coke, calcined needle coke, pitch coke, and metallurgical coke; optionally, the raw material can include one or more of petroleum coke, needle coke, and calcined needle coke. In one embodiment, the second raw material and / or the third raw material is needle coke.
[0134] In some embodiments, the sulfur content of the second raw material and / or the third raw material is ≤0.6% by mass, and the volatile components are ≤7% by mass. Here, the so-called volatile components refer to volatile organic matter, such as alkanes, aromatic hydrocarbons, lipids, etc. The sulfur content and volatile components of the second raw material and / or the third raw material are within the above ranges, which is conducive to reducing impurities in the second artificial graphite and the third artificial graphite obtained, improving the graphitization degree of the negative electrode active material, and thus improving the energy density of the secondary battery.
[0135] In the present application, the grading and screening can be achieved by using equipment known in the art without particular limitation. In some embodiments, the grading and screening can be performed by using a classifier. Exemplarily, the classifier is selected from a cyclone classifier and an air flow classifier.
[0136] In the present application, the second adhesive in the third artificial graphite preparation step can adopt an adhesive known in the art, without special restrictions. Exemplarily, the second adhesive may include one or more of oily asphalt, coal-based asphalt, high molecular polymer, etc. In some embodiments, in the third artificial graphite preparation step, the softening point of the second adhesive is ≥150°C. The use of an adhesive with a softening point within the above range has a high coking value and is easy to graphitize, which is beneficial to increase the powder compaction density of the third artificial graphite, thereby increasing the gram capacity of the negative electrode active material and the energy density of the secondary battery. In some optional embodiments, the softening point of the adhesive is 150°C-280°C. Exemplarily, the softening point of the adhesive may be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C or a value within a range consisting of any two of these values.
[0137] In some embodiments, in the third artificial graphite preparation step, the mass percentage of the second adhesive relative to the mass of the primary particles is 8%-14%. By making the mass of the binder within the above range, it is beneficial to achieve better bonding and improve the isotropy of the secondary particles. Exemplarily, the mass percentage of the second adhesive relative to the mass of the primary particles can be 8%, 9%, 10%, 11%, 12%, 13%, 14% or a value between the ranges consisting of any two of them.
[0138] In some embodiments, in the mixing step, the ratio of the second artificial graphite to the third artificial graphite is 1:9 to 3:7. By making the mass ratio of the second artificial graphite and the third artificial graphite within the above range, it is beneficial to adjust the powder OI value and the powder compaction density of the second negative electrode active material, so that the second negative electrode active material can take into account good kinetic performance and high energy density and good cycle performance. Exemplarily, the mass ratio of the second artificial graphite and the third artificial graphite can be 3:7, 1:3, 1:4, 5:17, 1:9 or a value between the ranges consisting of any two ratios thereof. In one embodiment, the mass ratio of the second artificial graphite and the third artificial graphite is 1:9 to 1:3. In an optional embodiment, the mass ratio of the second artificial graphite and the third artificial graphite is 1:3.
[0139] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0140] In some embodiments, the first negative electrode active material and the optional conductive agent, the optional binder and other optional additives can be dispersed in a solvent (e.g., deionized water) to form a first slurry. The second negative electrode active material and the optional conductive agent, the optional binder and other optional additives can be dispersed in a solvent (e.g., deionized water) to form a second slurry. The above-mentioned binder can be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The conductive agent can be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, the negative electrode film layer may also optionally include other additives, such as a thickener (e.g., sodium carboxymethyl cellulose (CMC-Na)).
[0141] Positive electrode
[0142] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0143] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0144] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0145] In some embodiments, when the battery cell is a lithium-ion battery, the positive electrode active material may adopt a positive electrode active material for lithium-ion batteries that is well known in the art. As an example, the positive electrode active material may include at least one of the following materials: a lithium-containing phosphate with an olivine structure, a lithium transition metal oxide, and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.1 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0146] It should be noted that in the embodiments of the present application, the above chemical formula is the chemical formula of the material used in the secondary battery preparation process. In the positive electrode sheet, battery cell, and electrical equipment, due to the formation and circulation processes, those skilled in the art can understand that the elements in the above chemical formula may be lost. For example, in the positive electrode sheet, battery cell, and electrical equipment, due to the circulation process, the oxygen element in the positive electrode active material is lost, so the measured oxygen content in the positive electrode active material will be reduced.
[0147] It should be noted that in the positive electrode sheets, battery cells, and electrical equipment, lithium ions will be consumed during the formation and circulation processes, so the measured lithium content in the positive electrode active material will decrease. At the same time, if the positive and negative electrode sheets are supplemented with lithium, after the formation and circulation processes, the measured lithium content in the positive electrode active material will increase.
[0148] The battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0149] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.
[0150] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0151] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0152] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0153] Electrolytes
[0154] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0155] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0156] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0157] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0158] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0159] Isolation film
[0160] In some embodiments, the battery cell further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0161] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0162] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0163] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0164] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0165] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 2 The battery cell 5 is a square structure as an example.
[0166] In some embodiments, reference Figure 3 , the outer packaging may include a shell 51 and a top cover assembly 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the top cover assembly 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0167] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0168] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0169] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0170] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0171] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0172] In addition, the present application also provides an electric device, which includes a secondary battery provided in the present application. The secondary battery can be used as a power source for the electric device, or as an energy storage unit for the electric device. The electric device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0173] As the electrical device, a battery cell, a battery module or a battery pack can be selected according to its usage requirements.
[0174] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.
[0175] As another example, the device may be a mobile phone, a tablet computer, a notebook computer, etc. The device is usually required to be light and thin, and a battery cell may be used as a power source.
[0176] Example
[0177] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0178] Preparation of the first negative electrode active material
[0179] Materials 1-1
[0180] Step 1: crushing and shaping the oil-based calcined needle coke raw material (carbon content of 98.5%, volatile content of 1.0%, sulfur content of 0.5%) by jet mill to obtain a shaped material with a Dv50 of 11 μm;
[0181] Step 2: Use granulation asphalt with a softening point of 200° C. as the first adhesive to granulate the above-mentioned shaping material together through a granulation kettle to obtain granulated material, wherein the mass ratio of the shaping material to the first adhesive is 100:8.
[0182] Step 3: The granulated material is pre-carbonized at 1150° C. for 2 hours under a nitrogen atmosphere to obtain an intermediate.
[0183] Step 4: The intermediate is graphitized at a high temperature of 3020°C, and the graphitized particles are sieved and demagnetized to obtain the first artificial graphite with La (110) of 131.7nm and Lc (002) of 32.5nm as the first negative electrode active material 1-1.
[0184] Materials 1-2 to 1-4 and materials 1-1' to 1-2'
[0185] The preparation methods of materials 1-2 to 1-4 and materials 1-1' to 1-2' are similar to that of material 1-2, except that the raw material type and graphitization temperature are adjusted so that the La(110), Lc(002), La / Lc, powder OI value, gram capacity, powder compaction density and Dv50 of materials 1-2 to 1-4 and materials 1-1' to 1-2' are the values shown in Table 1.
[0186] The above materials were tested according to the following method, and the results are shown in Table 1.
[0187] Tests of La(110), Lc(002), and La / Lc of materials:
[0188] Referring to the test method of JIS K 0131-1996, the test was carried out using a Bruker D8 Discover X-ray diffractometer, in which a copper target was used as the anode target, CuKα rays were used as the radiation source, and the ray wavelength was The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min to obtain the X-ray diffraction pattern of the powder sample. The La(110), Lc(002), and La / Lc of the material are calculated using the following formula:
[0189] La calculation formula:
[0190] Where: K is the shape factor, which is 1.84; λ is the wavelength (nm); β110 is the half-peak width of the 110 crystal plane corresponding to ~43° in the X-ray diffraction pattern; θ110 is the diffraction angle corresponding to the 110 crystal plane in the X-ray diffraction pattern
[0191] Lc calculation formula:
[0192] Where: K is the shape factor, which is 0.89; λ is the wavelength (nm); β002 is the half-peak width of the 002 crystal plane corresponding to ~26° in the X-ray diffraction spectrum; θ002 is the diffraction angle corresponding to the 002 crystal plane in the X-ray diffraction spectrum
[0193] Test of OI value of powder material :
[0194] According to the lattice parameter test method of artificial graphite in JB / T 4220-2011, the test was carried out using a Bruker D8Discover X-ray diffractometer, in which a copper target was used as the anode target and CuKα rays were used as the radiation source. The wavelength of the rays was The scanning 2θ angle range is 20°-80°, and the scanning rate is 4° / min to obtain the X-ray diffraction spectrum of the material. The integral area I of the diffraction peak of the crystalline carbon 004 crystal plane in the powder sample is calculated based on the X-ray diffraction spectrum. 004 , and the integrated area I of the diffraction peak of the crystalline carbon 110 plane in the powder sample 110 The powder OI adopts the formula OI value = I 004 / I 110 to calculate.
[0195] Test of Gram Capacity of Materials :
[0196] The prepared materials, conductive agent carbon black (Super P), binder polyvinylidene fluoride (PVDF) and solvent N-methylpyrrolidone (NMP) are mixed uniformly in a mass ratio of 91.6:1.8:6.6 to prepare a slurry; the prepared slurry is coated on the surface of the negative electrode current collector copper foil, dried in an oven and set aside; ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L; then a metal lithium sheet is used as a counter electrode and a polyethylene (PE) film is used as an isolation membrane, and the above electrolyte is assembled into a CR2430 button battery in an argon-protected glove box; the obtained button battery is left to stand for 12 hours.
[0197] At 25°C, the button cell prepared above was first discharged at a constant current of 0.15 mA to 0.005 V, allowed to stand for 5 minutes, then discharged at a constant current of 50 μA to 0.005 V, allowed to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V, and the first-cycle discharge capacity of the button cell was recorded; thereafter, the button cell was charged at a constant current of 0.3 mA to 2.0 V, and the first-cycle charging capacity of the button cell was recorded. The ratio of the first-cycle charging capacity to the mass of the material is the gram capacity of the material.
[0198] The proportion of the platform's lithium-ion capacity to the total capacity is X
[0199] The CR2430 button cell was prepared by the same method as in the above-mentioned gram capacity test method. After the above-mentioned CR2430 button cell was allowed to stand for 12 hours, it was first discharged at a constant current of 0.15 mA to 0.005 V at 25°C, allowed to stand for 5 minutes, and then discharged at a constant current of 50 μA to 0.005 V again, allowed to stand for 5 minutes, and then discharged at a constant current of 10 μA to 0.005 V again; then it was charged at a constant current of 0.3 mA to 2.0 V, and the relationship between the charge and discharge capacity and voltage of the material was obtained, that is, the charge and discharge curve. The lithium insertion capacity of the lithium insertion platform that appears within 0.005V-0.070V in the discharge curve is recorded as C1, and the total lithium insertion capacity within the range of 0.005V-2.0V is recorded as C2, then the lithium insertion capacity of the platform accounts for X=C1 / C2*100%.
[0200] Testing of the compacted density of powder materials :
[0201] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument, set the pressure to 50000N, and the thickness of the powder under the pressure (thickness after pressure relief) can be read on the equipment. The compaction density can be calculated through ρ=m / v.
[0202] Volume distribution particle size test of materials :
[0203] Dv50 test: referring to GB / T 19077-2016 particle size distribution laser diffraction method, the test was carried out using Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK.
[0204] (Dv90-Dv10) / Dv50: Referring to GB / T 19077-2016 particle size distribution laser diffraction method, the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd. of the United Kingdom was used to test the values of Dv90, Dv50 and Dv10 respectively, and the value of (Dv90-Dv10) / Dv50 was calculated.
[0205] Table 1
[0206]
[0207] Preparation of the Second Negative Electrode Active Material
[0208] (1) Preparation of the Second Artificial Graphite
[0209] Material a-1
[0210] Step 1: The needle-shaped green coke (sulfur content of 0.5% and volatile matter of 5%) is crushed and shaped by a mechanical mill, and then classified by an air flow classifier to remove small particles to obtain a shaped material.
[0211] Step 2: Graphitize the above-mentioned shaped material at a high temperature of 3100°C and graphitize it in an Acheson graphitization furnace for 36 hours; screen and demagnetize the graphitized particles to obtain primary particles with a Dv50 of 7μm and a Dv1 of 3.5μm as the second artificial graphite (material a-1).
[0212] Material a-2 to material a-3
[0213] The preparation methods of materials a-2 to a-3 are similar to those of material a-1, except that the type of raw materials and the graphitization temperature are adjusted, and the Dv1, Dv50, powder OI value, gram capacity and powder compaction density of the obtained materials a-2 to a-3 are the values shown in Table 2.
[0214] Table 2
[0215]
[0216] (2) Preparation of the third artificial graphite
[0217] Material b-1
[0218] Step 1: Use a jet mill to crush and shape needle-shaped green coke (sulfur content 0.5%, volatile matter 5%) to obtain primary particles with a Dv50 of 8.0 μm.
[0219] Step 2: Use oily asphalt with a softening point of 180°C as a binder and granulate the primary particles together through a granulation kettle to obtain granules. The amount of the binder added is 10% relative to the total weight of the granules.
[0220] Step 3: Graphitize the above granulated material at a high temperature of 3100°C for 36 hours; screen and demagnetize the graphitized particles to obtain secondary particles with a Dv50 of 14.5 μm as the third artificial graphite (material b-1).
[0221] Material b-2 to material b-3
[0222] The preparation method of materials b-2 to b-3 is similar to that of material b-1, except that the raw materials and graphitization temperature of materials b-2 to b-3 are adjusted so that the Dv50, powder OI value, gram capacity and powder compaction density under a pressure of 50,000 N of the material are the values shown in Table 3.
[0223] The particle size, OI value, gram capacity and powder compaction density of the material were tested using the same method as the third artificial graphite mentioned above, and the test results are recorded in Table 3.
[0224] Table 3
[0225]
[0226] (3) Preparation of the Second Negative Electrode Active Material
[0227] The second artificial graphite and the third artificial graphite were mixed according to the mass ratio shown in Table 4 below to obtain a second negative electrode active material.
[0228] The above test method was used for testing, and the test results are shown in Table 4.
[0229] Table 4
[0230]
[0231] Example 1
[0232] (1) Preparation of the first negative electrode active material slurry
[0233] The first negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 96.6:0.80:1.0:1.6 to form a first negative electrode active material slurry.
[0234] (2) Preparation of Second Negative Electrode Active Material Slurry
[0235] The second negative electrode active material, conductive agent Super P, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber were fully stirred and mixed in a proper amount of solvent deionized water at a weight ratio of 97.4:1:0.7:0.9 to form a first negative electrode active material slurry.
[0236] (3) Preparation of negative electrode sheet
[0237] The first negative electrode active material slurry and the second negative electrode active material slurry are extruded simultaneously by a double-chamber coating device, wherein the mass ratio of the first negative electrode active material slurry to the second negative electrode active material slurry is 1:1. The first negative electrode active material slurry is coated on the negative electrode current collector copper foil, that is, the first negative electrode active material slurry is coated on the first region, and the second negative electrode active material slurry is coated on the first negative electrode active material slurry, that is, the second negative electrode active material slurry is coated on the second region. After drying and cold pressing, a negative electrode sheet is obtained.
[0238] (4) Preparation of positive electrode sheet
[0239] Lithium iron phosphate: conductive carbon black: PVDF = 96.2:2:1.8 was mixed in a mass ratio, and then solvent N-methylpyrrolidone was added and stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was coated on both surfaces of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet was obtained.
[0240] (5) Preparation of lithium-ion batteries
[0241] A 7μm polyethylene film is used as the separator, PVDF slurry is sprayed on both sides of the separator, and a 1μm alumina ceramic coating is sprayed on one side, and the ceramic coating side corresponds to the cathode electrode.
[0242] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then LiPF6 is dissolved in the above organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0243] The positive electrode sheet and negative electrode sheet prepared above are placed in order, so that the isolation film is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then the electrode assembly is obtained by winding; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and a secondary battery is obtained after vacuum packaging, standing, forming, shaping and other processes.
[0244] Embodiment 2-4
[0245] The battery preparation methods of Examples 2-4 are similar to those of Example 1, except that, in the step of preparing the negative electrode sheet, the types of the first negative electrode active material and the second negative electrode active material are adjusted as shown in Table 5.
[0246] Comparative Example 1
[0247] The battery preparation method of Comparative Example 1 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, the second negative electrode active material slurry is coated on the first region, and the first negative electrode active material slurry is coated on the second region.
[0248] Comparative Example 2
[0249] The battery preparation method of Comparative Example 2 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, the first negative electrode active material and the second negative electrode active material are mixed and then coated on the negative electrode current collector to form a single-layer negative electrode film layer.
[0250] Comparative Example 3
[0251] The battery preparation method of Comparative Example 3 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, only the first negative electrode active material 1-1 is used to form a single negative electrode film layer on the negative electrode current collector.
[0252] Comparative Example 4
[0253] The battery preparation method of Comparative Example 4 is similar to that of Example 1, except that, in the step of preparing the negative electrode sheet, only the second negative electrode active material 2-1 is used to form a single negative electrode film layer on the negative electrode current collector.
[0254] Comparative Examples 5-6
[0255] The battery preparation method of Comparative Examples 5-6 is similar to that of Example 1, except that, in the preparation step of the negative electrode sheet, the types of the first negative electrode active material and the second negative electrode active material are adjusted as shown in Table 5.
[0256] Performance Testing
[0257] (1) Energy density
[0258] At 25°C, the secondary battery was charged to 3.65V at 1 / 3C constant current, then charged to 0.05C at 3.65V, left to stand for 5 minutes, and then discharged to 2.5V at 1 / 3C constant current, and the battery discharge energy was recorded. The battery discharge energy divided by the battery weight is the battery weight energy density, in Wh / kg. The measurement data is shown in Table 5.
[0259] (2) Rapid charging performance test of secondary batteries
[0260] At 25°C, the secondary battery was charged to 3.65V at a constant current of 0.33C, then charged to a current of 0.05C at a constant voltage, and after standing for 5 minutes, the secondary battery was discharged to 2.0V at a constant current of 0.33C, and its actual capacity was recorded as C0.
[0261] Then the secondary battery is charged with constant current at 1.0C0, 1.3C0, 1.5C0, 1.8C0, 2.0C0, 2.3C0, 2.5C0, 3.0C0 in sequence to 3.65V or 0V negative electrode cut-off potential (whichever is reached first). After each charge, it is discharged to 2.0V at 1C0. Record the SOC (State of Charge) at different charge rates to 10%, 20%, 30%, ..., 80%. The charge rate-negative electrode potential curve under different SOC states is drawn, and the charge rate corresponding to the negative electrode potential of 0V under different SOC states is obtained after linear fitting. The charge rate is the charging window under the SOC state, which is recorded as C10% SOC, C20% SOC, C30% SOC, C40% SOC, C50% SOC, C60% SOC, C70% SOC, C80% SOC respectively. The charging time T of the secondary battery from 10% SOC to 80% SOC (under the premise that the secondary battery does not precipitate lithium) is calculated according to the following formula, in min. The shorter the charging time, the better the kinetic performance of the secondary battery:
[0262] T=(60 / C10%SOC+60 / C20%SOC+60 / C30%SOC+60 / C40%SOC+60 / C50%SOC+60 / C60%SOC+60 / C70%SOC+60 / C80%SOC)×10%
[0263] (3) Cycle performance test of secondary batteries
[0264] At 45°C, the secondary battery was charged at 1C constant current to an upper limit of 3.65V (corresponding to 100% SOC), then charged at constant voltage to a current of 0.05C. After standing for 5 minutes, the secondary battery was discharged at 1C constant current to 2.5V (corresponding to 0% SOC), and the discharge capacity at this time was recorded, which was the discharge capacity of the first cycle. The secondary battery was subjected to cyclic charge and discharge tests according to the above method, and the discharge capacity after each cycle was recorded.
[0265] Capacity retention rate (%) of secondary battery after 1000 cycles at 45° C.=discharge capacity after 1000 cycles / discharge capacity at the first cycle×100%.
[0266] The secondary batteries prepared in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 5.
[0267] Table 5
[0268]
[0269] According to the data in Table 5, it can be seen that compared with Comparative Examples 1 to 6, in the negative electrode sheets prepared in the embodiments of the present application, the negative electrode film layer is a double-layer design, the first region adopts a first negative electrode active material with high energy density, and the second region adopts a second negative electrode active material with high isotropy and high powder compaction density. As a result, the secondary battery can take into account high energy density, excellent kinetic performance and high cycle performance.
[0270] Example 5-11
[0271] The battery preparation methods of Examples 5-11 are similar to those of Example 1, except that, in the preparation step of the negative electrode sheet, the type of the second negative electrode active material and the mass ratio of the first negative electrode active material to the second negative electrode active material are adjusted as shown in Table 6.
[0272] The performance of the secondary battery prepared in the above embodiment was tested, and the results are shown in Table 6.
[0273] Table 6
[0274]
[0275] From the data in Table 6, it can be seen that the secondary battery prepared in the embodiments of the present application can have both high energy density and excellent kinetic performance and high cycle performance.
[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A secondary battery, comprising a negative electrode plate, characterized in that: The negative electrode plate includes a negative electrode current collector and a negative electrode film layer formed on at least one surface of the negative electrode current collector, the negative electrode film layer includes a first region and a second region, the first region is located between the second region and the negative electrode current collector, the first region includes a first negative electrode active material, the second region includes a second negative electrode active material, the powder OI value of the second negative electrode active material is less than the powder OI value of the first negative electrode active material, the first negative electrode active material includes a first artificial graphite, La(110) of the first artificial graphite is 130nm-175nm, and Lc(002) is 30nm-42nm, La(110) represents the crystallite size along the a-axis in the (110) crystal plane of the first artificial graphite, and Lc(002) represents the crystallite size along the c-axis in the (002) crystal plane of the first artificial graphite.
2. The secondary battery according to claim 1, characterized in that: The La(110) of the first artificial graphite is 132nm-172nm, and / or the Lc(002) is 30nm-36nm.
3. The secondary battery according to claim 1 or 2, characterized in that: La(110) / Lc(002) is 3.5-5.
5.
4. The secondary battery according to any one of claims 1 to 3, characterized in that: La(110) / Lc(002) is 4.5-5.
5.
5. The secondary battery according to any one of claims 1 to 4, characterized in that: The button cell prepared by the first artificial graphite was subjected to charge and discharge tests under the conditions of a lithium desorption rate of 0.1C and a lithium insertion rate of 0.05C, respectively, to obtain a charge and discharge curve in the range of 0.005V-2.0V. In the discharge curve, there is a lithium insertion platform in the voltage range of 0.005V-0.070V, and the proportion X of the discharge capacity corresponding to the lithium insertion platform to the total discharge capacity of the button cell is more than 43%.
6. The secondary battery according to claim 5, characterized in that: The proportion X of the discharge capacity corresponding to the lithium embedded platform to the total discharge capacity of the button cell is 43%-47%.
7. The secondary battery according to any one of claims 1 to 6, characterized in that: The gram capacity of the first negative electrode active material is greater than or equal to the gram capacity of the second negative electrode active material.
8. The secondary battery according to any one of claims 1 to 7, characterized in that: The gram capacity of the first negative electrode active material is ≥359 mAh / g; and / or, The gram capacity of the second negative electrode active material is 353 mAh / g-359 mAh / g.
9. The secondary battery according to any one of claims 1 to 8, characterized in that: The gram capacity of the first negative electrode active material is 359 mAh / g-366 mAh / g; and / or, The gram capacity of the second negative electrode active material is 354.6 mAh / g-356.8 mAh / g.
10. The secondary battery according to any one of claims 1 to 9, characterized in that: The first negative electrode active material has a greater degree of graphitization than the second negative electrode active material.
11. The secondary battery according to any one of claims 1 to 10, characterized in that: The graphitization degree of the first negative electrode active material is 94.0%-96.0%; and / or, The graphitization degree of the second negative electrode active material is 93.5%-95.5%.
12. The secondary battery according to any one of claims 1 to 11, characterized in that: The graphitization degree of the first negative electrode active material is 94.2%-95.8%; and / or, The graphitization degree of the second negative electrode active material is 93.7%-95.3%.
13. The secondary battery according to any one of claims 1 to 12, characterized in that: The powder compaction density of the first negative electrode active material under a pressure of 50000N is greater than the powder compaction density of the second negative electrode active material under a pressure of 50000N.
14. The secondary battery according to any one of claims 1 to 13, characterized in that: The first negative electrode active material has a powder compaction density of 1.95 g / cc to 2.04 g / cc under a pressure of 50000 N; and / or, The powder compaction density of the second negative electrode active material under a pressure of 50000N is 1.75g / cc-1.94g / cc.
15. The secondary battery according to any one of claims 1 to 14, characterized in that: The first artificial graphite includes secondary particles.
16. The secondary battery according to any one of claims 1 to 15, characterized in that: The powder OI value of the first negative electrode active material is 5.0-20.5; and / or, The powder OI value of the second negative electrode active material is 2.5-6.
5.
17. The secondary battery according to any one of claims 1 to 16, characterized in that: The powder OI value of the first negative electrode active material is 5.5-19.5; and / or, The OI value of the second negative electrode active material is 2.8-6.
3.
18. The secondary battery according to any one of claims 1 to 17, characterized in that: The volume distribution particle size Dv50 of the second negative electrode active material is 10.0 μm-15.5 μm; and / or, The particle size distribution of the second negative electrode active material is (Dv90-Dv10) / Dv50 is 0.95-1.
3.
19. The secondary battery according to any one of claims 1 to 18, characterized in that: The volume distribution particle size Dv50 of the second negative electrode active material is 11.0 μm-14.5 μm; and / or, The particle size distribution of the second negative electrode active material is (Dv90-Dv10) / Dv50 is 0.95-1.
25.
20. The secondary battery according to any one of claims 1 to 19, characterized in that: In the second negative electrode active material, the volume distribution proportion of particles with a particle size greater than 6.5 μm and less than 22.5 μm is ≥75%.
21. The secondary battery according to any one of claims 1 to 20, characterized in that: In the second negative electrode active material, the volume distribution of particles with a particle size greater than 6.5 μm and less than 22.5 μm accounts for 75%-90%.
22. The secondary battery according to any one of claims 1 to 21, characterized in that: The second negative electrode active material includes a second artificial graphite and a third artificial graphite, the second artificial graphite includes primary particles, and the third artificial graphite includes secondary particles.
23. The secondary battery according to claim 22, characterized in that: In the second negative electrode active material, a mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 3:
7.
24. The secondary battery according to claim 22 or 23, characterized in that: In the second negative electrode active material, a mass ratio of the second artificial graphite to the third artificial graphite is 1:9 to 1:
3.
25. The secondary battery according to any one of claims 22 to 24, characterized in that: La(110) of the first artificial graphite is greater than La(110) of the second artificial graphite, and La(110) of the first artificial graphite is greater than La(110) of the third artificial graphite.
26. The secondary battery according to any one of claims 22 to 25, characterized in that: The La(110) of the second artificial graphite is 100-140nm, and the Lc(002) is 25-32nm.
27. The secondary battery according to any one of claims 22 to 26, characterized in that: The La(110) of the third artificial graphite is 90-130nm, and the Lc(002) is 26-34nm.
28. The secondary battery according to any one of claims 22 to 27, characterized in that: The volume distribution particle size Dv50 of the second artificial graphite is 7 μm-9 μm, and Dv1 is 3 μm-5.5 μm; and / or, The volume distribution particle size Dv50 of the third artificial graphite is 13 μm-18 μm.
29. The secondary battery according to any one of claims 22 to 28, characterized in that: The OI value of the second artificial graphite powder is 7-10; and / or, The powder OI value of the third artificial graphite is 2-5.
30. The secondary battery according to any one of claims 22 to 296, characterized in that: The gram capacity of the second artificial graphite is 354.1 mAh / g to 359.6 mAh / g; and / or, The gram capacity of the third artificial graphite is 353.0 mAh / g to 358.2 mAh / g.
31. The secondary battery according to any one of claims 22 to 30, characterized in that: The second artificial graphite has a powder compaction density of 1.72 g / cc to 1.92 g / cc under a pressure of 50000 N; and / or, The powder compaction density of the third artificial graphite under a pressure of 50000N is 1.75g / cc to 1.95g / cc.
32. The secondary battery according to any one of claims 1 to 31, characterized in that: The first artificial graphite satisfies one or more of the following conditions: (1) The volume distribution particle size Dv50 of the first artificial graphite is 14.5 μm-18.0 μm; (2) the particle size distribution of the first artificial graphite (Dv90-Dv10) / Dv50 is 0.90-1.25; (3) The specific surface area of the first artificial graphite is 0.8 m 2 / g-2.1m 2 / g.
33. The secondary battery according to any one of claims 1 to 32, characterized in that: The first artificial graphite satisfies at least one or more of the following conditions: (1) The volume distribution particle size Dv50 of the first artificial graphite is 15.0 μm-17.5 μm; (2) the particle size distribution of the first artificial graphite (Dv90-Dv10) / Dv50 is 0.90-1.20; (3) The specific surface area of the first artificial graphite is 1.0 m 2 / g-1.9m 2 / g.
34. The negative electrode sheet according to any one of claims 1 to 33, characterized in that: The first negative electrode material and / or the second negative electrode active material further comprises silicon.
35. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 1 to 34.
Citation Information
Patent Citations
Composite negative electrode active material, preparation method thereof and negative electrode
CN109962213A
Secondary battery and device containing same
CN113228341A
Secondary battery, method for preparing same, and battery module, battery pack and device including same
CN114747042A
Secondary battery and electric device
CN117558918A
Negative electrode material, secondary battery, and electronic device
CN117882216A